Pembelajaran dengan Layanan Bimbingan Klasikal Teknik Case Method dalam Upaya Meningkatkan Tanggung Jawab Akademik Siswa - Arini, Intan; Hariyadi, Sigit (Jurnal Studi Multidisiplin Qomaruna, 2024)
This study is motivated by the low levels of academic responsibility among students, which remains challenging in the educational environment. The study aims to evaluate the effectiveness of classical guidance services using the case method technique to improve students' academic responsibility. The research employed a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest design. The intervention was conducted in seven sessions over one month, involving 32 eleventh-grade students selected through purposive sampling. Data were collected using an academic responsibility scale developed based on Mergler's (2017) theory, with instrument validity ranging from 0.323 to 0.503 and reliability of 0.778. The analysis results using a t-test showed a t-value of 12.673 with a p-value <0.001, indicating that classical guidance services using the case method technique effectively enhanced students' academic responsibility. These findings can serve as a reference for developing strategies to improve students' academic responsibility and support teaching and learning activities in schools. Future research will explore different variables, interventions, and methods to broaden insights and compare findings